Study of Various Testing Techniques With Respect To Application Software - Chaplot, Vivek (International Journal of Computer Sciences and Engineering, 2025)
Any Software which is created for some purpse will be true software if it is tested properly. Testing is very essential component of Software Development Life Cycle .Testing is process of finding whether the program meets required specification or not. Testing is very important for performance and usability. It is process of analysing and evaluating the system components. In this we analyse difference between actual result and expected result is studied